Evaluasi Beban Kerja Mental Menggunakan Metode NASA-TLX pada Operator Call Center di PT. XYZ Makassar - Ahmad, Fauziah (Journal of Industrial System Engineering and Management, 2024)
This study examines the mental workload experienced by call center operators at PT XYZ Makassar using the NASA-TLX method. High mental workload can impact service quality, productivity, and employees' psychological well-being, particularly in high-pressure service industries. The aim of this study is to identify the dominant dimensions of mental workload and analyze their relationship with the work conditions of call center operators. A mixed-methods approach was employed, focusing on descriptive quantitative analysis, complemented by qualitative data through semi-structured interviews. The primary instrument used was the NASA-TLX, which measures mental workload based on six dimensions: mental demand, physical demand, temporal demand, performance, effort, and frustration. The study involved 20 call center operators at PT XYZ Makassar. The findings reveal that 60% of operators experience high levels of mental workload, with effort and mental demand being the primary contributing factors. These findings indicate the need for improvements in workload management, such as restructuring work schedules, stress management training, and enhancing psychosocial support to alleviate excessive mental workload. This study contributes to the development of cognitive ergonomics theory in the service sector context and provides practical recommendations for improving employee well-being and operational efficiency. Further research could explore the long-term effects of mental workload on employee health and performance in other sectors.